Pendeteksian Fraud Pada Tata Kelola Penatausahaan Persediaan Badan Layanan Umum - Anggraeni, Devi Puspita (Jurnal Ekonomi Modernisasi, 2018)
This study aims to analyze and interpret fraud detection on the governance of the BLU inventory administration of University X. This study uses a qualitative approach that focuses on the case study method with the interpretive paradigm. Inventory administration activities at the University of x are inseparable from various obstacles. Such as the lack of coordination between work units in each unit. The results show that inventory administration activities in the University X run less optimally. The finding reveals the problem of financial statement misstatement in the inventory account due to the inconsistency of the operator in entering the exit price (value) of the inventory. So when at the end of the period there is a significant difference in material value (material). The results of this study also provide information about the effectiveness of the accounting system